CONCERNS ABOUT FIBROADENOMA EXCISION IN YOUNG FEMALE PATIENTS VIA CIRCUMAREOLAR VERSUS RADIAL INCISION - ALAM, SI; HUSSAIN, Y; ALI, N; ASHRAF , M; HUSSAIN, S; NISAR, W (Biological and Clinical Sciences Research Journal, 2024)
Fibroadenoma is the most common benign breast tumour in young female patients between 15 to 30 years of age. Lumpectomy is the most common surgical procedure, usually carried out via Circumareolar or Radial incisions depending upon size and location in the breast. Both of these incisions for lumpectomy have advantages and disadvantages of their own. In this study, we compared the outcome in terms of healing of wounds, Aesthetics and patient satisfaction. Objective: The purpose of this study was to evaluate the effectiveness of Circumareolar and Radial incision for lumpectomy, Aesthetic outcome and patient satisfaction in young female patients who opted for surgical excision. Methods: After ethical approval from the Hospital ethical committee and informed written consent from the participants; 189 patients were included and equally divided into Group A for Circumareolar incision and into Group B for Radial Incision participants, who met inclusion and exclusion criteria for this study. Data was collected by the Concerned Surgeon on a Pre-Designed Questionnaire in the District Headquarters Teaching Hospital, Kohat Development Authority Kohat from January 2021 to July 2021. Data was analyzed and shown in Tables. Results: The results demonstrate a significant preference for the circumareolar incision over the radial incision in the excision of large and peripherally located fibroadenomas among young female patients. A higher percentage of young female patients (63.04%) underwent circumareolar incision, reporting shorter recovery times (mean = 2.04 weeks) and greater satisfaction with the surgical outcome (mean satisfaction score = 5.43), compared to those who had a radial incision (37.25% underwent the procedure, with mean recovery time = 0.91 weeks and mean satisfaction score = 0.03). Statistical analysis further supports the efficacy of the circumareolar approach over the radial one, with significant differences in both recovery time and satisfaction levels (p < 0.000 for both measures), indicating its effectiveness and patient preference. Conclusion: Circumareolar incision is the best incision for large and peripherally located fibroadenoma excision in young female patients without any further morbidity or compromising quality of life.